The role of low molecular weight organic acids in the release of phosphorus from sewage sludge-based biochar. Issue 1 (1st January 2021) - Paul, Chandra Sekhar; Mercl, Filip; Száková, Jiřina; Tejnecký, Václav; Tlustoš, Pavel
Abstract : Low molecular weight organic acids (LMWOAs) are common and abundant compounds in the environment, responsible for the release of the nutrients from rhizosphere into the soil solution and, therefore, facilitating the availability of these nutrients for plants. Sewage sludge biochar (SSB) is considered to be a potential source of phosphorus (P) in soil. In this context, the efficacy of twelve LMWOAs in releasing SSB-bearing P was tested in a laboratory extraction experiment. Moreover, the potential effects of (i) biochar pyrolysis temperature (varying from 220°C to 620°C) and (ii) other elements in SS, to estimate the P bonds attacked predominantly by the LMWOAs, were also assessed. The results revealed citric acid was the most effective extraction agent enhancing the mobility of the SSB-derived P. P release was strongly affected by biochar pyrolysis temperature (the highest P release was from the 320°C biochar, significant at p  < 0.05). Moreover, the results showed that P was released preferably from Fe-P bearing compounds in SS. Citric acid was recorded as less effective at releasing other nutrients, such as Ca, Mg, K, indicating the exceptional performance of citric acid in P release from biochar without substantial effect on the other nutrients.